Current management of occult bacteremia in infants - Eduardo Mekitarian Filho; Werther Brunow de Carvalho (Brazilian Society of Pediatrics, 2015)
Objectives: To summarize the main clinical entities associated with fever without source (FWS) in infants, as well as the clinical management of children with occult bacteremia, emphasizing laboratory tests and empirical antibiotics. Sources: A non‐systematic review was conducted in the following databases-PubMed, EMBASE, and SciELO, between 2006 and 2015. Summary of the findings: The prevalence of occult bacteremia has been decreasing dramatically in the past few years, due to conjugated vaccination against Streptococcus pneumoniae and Neisseria meningitidis. Additionally, fewer requests for complete blood count and blood cultures have been made for children older than 3 months presenting with FWS. Urinary tract infection is the most prevalent bacterial infection in children with FWS. Some known algorithms, such as Boston and Rochester, can guide the initial risk stratification for occult bacteremia in febrile infants younger than 3 months. Conclusions: There is no single algorithm to estimate the risk of occult bacteremia in febrile infants, but pediatricians should strongly consider outpatient management in fully vaccinated infants older than 3 months with FWS and good general status. Updated data about the incidence of occult bacteremia in this environment after conjugated vaccination are needed.